LAMUT DAN MADIHIN Kesenian Tradisional Banjar di Tengah Arus Modernisasi - Jahdiah, Jahdiah (Fakultas Ilmu Budaya Universitas Diponegoro, 2012)
There are various types of Banjar traditional arts flourishing in South Kalimantan. Among others are rare types of traditional arts that are feared to be extinct. Lamut is one of those rare types of traditional arts, while Madihin seems to have significant progress. In performing Lamut, a big tambourine is played as an interlude by a palamutan, while Madihin is performed by a madihin artist called pemadihinan who also plays a tambourine. The tambourine is played by using two hands beating the tambourine in stomping rhythm of the opening, content and the act of performing rhyming quatrains.